Intra-rater reliability of transversus abdominis measurement by a novice examiner: Comparison of "freehand" to "probe force device" method of real-time ultrasound imaging. (August 2019) - Kennedy, Vanessa L; Flavell, Carol A; Doma, Kenji
A "free hand" real-time-ultrasound method is commonly applied to measure transversus abdominis. Potentially, this increases transversus abdominis measurement error due to uncontrolled variability in probe to skin force, inclination, and roll, particularly for novice examiners. This single-group repeated-measures reliability study compared the intra-rater reliability of transversus abdominis thickness and activation measurement by a novice examiner between free hand and a standardized probe force device method. The examiner captured ultrasound videos of transversus abdominis in a single session in healthy participants ( n = 33). Free hand ultrasound featured uncontrolled probe force, inclination, and roll, while probe force device method ultrasound standardized these parameters. Images of transversus abdominis at rest and contracted were measured and transversus abdominis activation calculated. Intraclass correlation coefficient, coefficient of variation, standard error of measurement, and worthwhile differences were calculated. The probe force device method resulted in greater reliability (intraclass correlation coefficient = 0.75–0.96) and lower measurement error (coefficient of variation = 8.89–28.7%) compared to free hand (intraclass correlation coefficient = 0.63–0.93; coefficient of variation = 6.52–29.4%). Reliability was good for all measurements except free hand TrA-C, which was moderate. TrA-C had the lowest reliability, followed by contracted thickness of the transverse abdominis, with resting thickness of the transverse abdominis being highest. Worthwhile differences were lower using a probe force device method versus free hand for resting thickness of the transverse abdominis and contracted thickness of the transverse abdominis and similar for TrA-C. Standardization using probe force device method ultrasound to measure transversus abdominis improved intra-rater reliability in a novice examiner. Use of a probe force device method is recommended to improve reliability through reduced sources of measurement error. Probe force device method intra- and inter-rater reliability in examiners of varying experience, in clinical populations, and to visualize other structures merits exploration.